Sacralizing Clio: religion and design of History in public schools of Penapolis, SP (1990-2010) - Marotta Peters, Carlos Eduardo [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2016)
This article analyzes the inclusion of religious discourses on state schools in the city of Penapolis, Sao Paulo state (SP), between 1990 and 2010. It discusses the concept of history present in such discourses and how they were entered into the school routine. The work is inserted under the Cultural History category, from where it draws its fundamental concepts such as representation and symbolic power.
Keywords: Representation; Public School; Religion; Symbolic Power